Bioethics and genomics - Mainetti, José Alberto (Acta Bioethica, 2003)
The scientific advances in genomics open the door to human fears. For this reason, the Human Genome Project, HGP, has been the first great international research project that has had as subproject the associated Ethical, Legal, and Social Issues (ELSI). This bioethical worry arose as answer to the ethical and social questions that appearing in relation to the genomic advances. Genomics is shown as the key that will reveal the mystery of being (Aldine's lamp) or as tool of ecological destruction, as genetic determinism, as eugenic, that is to say, as Pandora's box. The HGP possesses an incalculable value for the diagnosis of new diseases, new medicines and new therapies, but it also brings some risks and fears that must be studied and analyze from a larger perspective than the scientific-technical, that is to say, as bioethical reflection genomics.